(3NGOe GdQhVI hGdQGaYis - (3HOQ GdOjf eMeO Hf HgGOQ Hf YHO Gddg GdRQcTis; (3GdRQcTj , eMeO Hf HgGOQ Hf YHO Gddg, HOQ GdOjf CHh YHO Gddg,J (B794 (3g` s
(3ChdgG (B:s
(3cJGH GdfcGM s
(3BNQgG (B:s
(3BNQ GdaUd GdSGOS ai GdTbGb s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B60 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B121s
Keywords: (3Gdabg GdTGaYjs